A New Four-Dimensional Chaotic System and its Circuit Implementation - Wang, Xuan; Feng, Yiran; Chen, Yixin (Frontiers in Physics, 2022)
A new four-dimensional chaotic system is designed in the paper. The equilibrium point and stability of the chaotic system are analyzed, and the dynamical behaviors of the system under different parameters are analyzed by using Lyapunov exponents, Bfurcation diagram, SE and C0 complexity algorithms. The special phenomenon of the coexistence of attractors is also found. Finally, the implementation of circuit of the new system is carried out using digital signal processing (DSP) technology, and the results are consistent with the numerical simulation results, which prove the validity of the theoretical analysis. Through analysis and simulation of the system, it can be found that it has relatively rich dynamic characteristics and can be applied in areas such as confidential communication and image encryption.